Unequal Partners: U.S. Collaboration with China and India in Research and Development. - Kennedy, Andrew B. (Political Science Quarterly (Oxford University Press / USA))
The article discusses the globalization of research and development (R&D), particularly whether the U.S. has become reliant upon China and India in R&D during the early 21st century and the potential impact on U.S. global standing in the post-Cold War era, arguing that while interdependence between the U.S. and China and India favors the U.S. politically, various constraints make it difficult for the U.S. to exploit its power. The article also examines the concepts of power and interdependence, as well as the economic agendas of the U.S., China, and India.